GE_GERICHTE P/19644/2017 vom 13. März 2018 - GE Cour de justice (2018)
VOL(DROIT PÉNAL) ; ADMINISTRATION DES PREUVES ; EXPULSION(DROIT PÉNAL) | CP.139; CP.172ter; CP.47; CP.49.al1; CP.66a.albis; LEtr.115.al1.letb; CPP.389.al1